Animal models of multiple sclerosis: From rodents to zebrafish. (March 2019) - Burrows, David John; McGown, Alexander; Jain, Saurabh A; De Felice, Milena; Ramesh, Tennore M; Sharrack, Basil; Majid, Arshad
Multiple sclerosis (MS) is a chronic, immune-mediated demyelinating disease of the central nervous system. Animal models of MS have been critical for elucidating MS pathological mechanisms and how they may be targeted for therapeutic intervention. Here we review the most commonly used animal models of MS. Although these animal models cannot fully replicate the MS disease course, a number of models have been developed to recapitulate certain stages. Experimental autoimmune encephalomyelitis (EAE) has been used to explore neuroinflammatory mechanisms and toxin-induced demyelinating models to further our understanding of oligodendrocyte biology, demyelination and remyelination. Zebrafish models of MS are emerging as a useful research tool to validate potential therapeutic candidates due to their rapid development and amenability to genetic manipulation.